Electroacupuncture Promotes Motor Function Recovery in MCAO/R Rats by Activating Astrocyte-Related PI3K/AKT Pathway - Xiao-Qing Zhang; Yi-He Wang; Li Sun; Bao-Qiang Dong; Yue-Jiao Sui; Jia-Zi Dong; Yang Han (Medical Association of Pharmacopuncture Institute, 2022)
Background : Electroacupuncture (EA) is a widely used traditional Chinese medicine method to manage various diseases, including cerebral ischemia-reperfusion injury (CIRI). Objectives: We assessed the neuroprotective effects of EA and examined its mechanism in a rat model of the middle cerebral artery occlusion-reperfusion (MCAO/R). The gait analysis was performed to evaluate the neuroprotective effects. Western blot and immunohistochemistry assays were carried out to determine the molecular mechanisms of EA. Methods : Male SD rats were randomly divided into the sham operation group, right MCAO/R group, and EA group. EA was administered every day (4/20 Hz, 10 min/1 d) at the following acupoints: Baihui (DU20), Yintang (EX-HN3), and Zusanli (ST36). Gait and motor function were analyzed from day 8 onward. Results : The plantar support and balance coordination of MCAO/R rats decreased, and the cellular structure of the ischemic penumbra was unclear. EA improved the gait dynamics of the rats, adjusted the cell structure, further activated astrocytes, and increased the expression and phosphorylation of phosphoinositide 3-kinase/protein kinase B (PI3K/PKB or AKT). Conclusion : EA promoted astrocyte-related effects in the rat model. Our findings suggest that the neuroprotective mechanism of EA may be related to the activation of the PI3K/AKT signaling pathway. The intervention enhanced brain protection and improved motor functions.